Loss of flavonoids homeostasis leads to pistillody in sua-CMS of Nicotiana tabacum - Jie Xu; Zhuo Wei; Jugou Liao; Keliang Tao; Junpeng Zhang; Yu Jiang; Yongzhi Niu; Yunye Zheng; Limeng Zhang; Xuemei Wei (BMC Plant Biology)
Abstract The homeotic transformation of stamens into pistil-like structures (pistillody) causes cytoplasmic male sterility (CMS). This phenomenon is widely present in plants, and might be induced by intracellular communication (mitochondrial retrograde signaling), but its systemic regulating mechanism is still unclear. In this study, morphological observation showed that the stamens transformed into pistil-like structures, leading to flat and dehiscent pistils, and fruit set decrease in sua-CMS (MS K326, somatic fusion between Nicotiana. tabacum L. K326 and Nicotiana suaveolens). Transcriptome data analysis presented that the expression levels of B-class MADS genes, including pMADS1, GLO1, GLO2, pMADS2.1, pMADS2.2, significantly reduced in the pistil-like structure of sua-CMS. DEGs were enriched in flavonoid and phenylpropanoid biosynthesis pathways. Transcriptome and metabolomics analysis revealed that the expression levels of CHI/CHS (key enzymes regulating flavonoid synthesis), and the contents of flavonoids reduced significantly in the pistil-like structures of sua-CMS. Chemical fluorescence staining assay showed that reactive oxygen species (ROS) levels were higher in the pistil-like structure of sua-CMS. Application of external flavonoids (hesperetin) reduced the frequency of pistillody and ROS levels. These results suggested that the metabolism of flavonoids played important roles in regulating pistillody through ROS in sua-CMS. Our study provides new insights into the regulatory mechanism of pistillody in plants.